Reasons for seeking treatment for cessation of Oral Habits - A Cross Sectional Study Among Parents. - K, AHMED HILAL SHERIFF; RAMAKRISHNAN, MAHESH; V, RAKSHAGAN (The journal of contemporary issues in business and government, 2021)
Oral habits like thumb sucking, lip/cheek biting and tongue thrusting may produce harmful effects on the development of maxillofacial regions which results in anterior open bite and posterior crossbites in growing children. The aim of this study was to assess the reasons for seeking treatment for cessation of oral habits of the children among the parents reporting to the department of pediatric dentistry. This was a retrospective study which was performed in a university setting where the required data of pediatric patients who were diagnosed with oral habits in the department of pedodontics at a private teaching hospital, Chennai from June 2019 to March 2020, was collected by reviewing patients records and the analysis of data of 86000 patients. The collected data was cross verified using photographs, reviewed by a reviewing expert and tabulated in Microsoft excel . The Sample size of the total number of patients diagnosed with oral habits seeking for treatment was n=24. The tabulated data was imported to SPSS software ( statistical package for social studies ) version 22.0 ( IBM corporation ) for statistical analysis .There was an equal gender distribution involved in this study. Regarding the awareness among the parents 50% of the parents were aware and 50% were not aware about the harmful oral habits of their children. There was no statistical significance among the gender, and oral habits and also the association between awareness of the parents and oral habits of the children. Thumb sucking habit was the most common habit among these patients(n=11), and incase of male children this habit was very common(n=7) while tongue thrusting habit was the most common among female children(n=5) and thumb sucking habit was the most commonly known habit among the parents(n=9).